Persistent Challenges and Barriers Encountered by Women Attending Formal Antenatal Care in South East Nigeria - Ohaja, Magdalena; Murphy-Lawless, Jo (Africa Journal of Nursing and Midwifery, 2018)
This paper presents the challenges and barriers to accessing formal maternity care in South East Nigeria from women’s perspectives. It is drawn from a study that explored the concept of safe motherhood. The study used a hermeneutic phenomenological approach guided by post-structural feminism. Data were collected through individual semi-structured interviews with 17 women who were attending a formal healthcare facility for antenatal care. Four aspects of the challenges and barriers encountered by women when accessing care in a formal healthcare setting as reported by the participants of the study are as follows: financial constraints, lack of autonomy, negative attitude of the healthcare providers, and healthcare worker strikes. Some participants linked the economic status of women to the lack of education which had an impact on their ability to make an independent decision as to whether to seek formal maternity healthcare or not. Negative attitudes, and frequent strikes of healthcare workers in many cases, discourage women from using the formal maternity healthcare facilities. It is evident that Nigeria did not achieve the Millennium Development Goal (MDG) 5, which is to improve maternal health. Achieving the Sustainable Development Goal (SDG) 3.1, which is to reduce the global maternal mortality ratio, requires more than technical approaches. Genuine political will is required if the health system is to be affordable for all women. There is the need to address the gender-related issues that sustain women’s low socio-economic status. The government needs to pay the workers as and when due, and a performance appraisal should be in place to ensure improvement in the quality of care offered to women.